Bortezomib-based consolidation or maintenance therapy for multiple myeloma: a meta-analysis - Zhang, Shijia (Blood Cancer J, 2020)
Bortezomib-based regimens are widely used as induction therapy for multiple myeloma (MM). Unlike lenalidomide, the role of bortezomib in consolidation and maintenance therapy for MM is less clear. We performed a meta-analysis to evaluate the impact of bortezomib-based consolidation and maintenance therapy on survival outcomes and adverse events. PubMed, Web of Science, Embase databases, and major conference proceedings were searched for randomized controlled trials (RCTs) of bortezomib-based regimens as consolidation or maintenance therapy for MM. Ten RCTs enrolling 3147 patients were included in the meta-analysis. Bortezomib-based regimens were compared with regimens without bortezomib or observation. The meta-analysis suggested that bortezomib-based maintenance therapy improved progression-free survival (PFS; hazard ratio [HR] = 0.72, 95% CI 0.55–0.95, P = 0.02) and overall survival (OS; HR = 0.71, 95% CI 0.58–0.87, P = 0.001). Bortezomib-based consolidation therapy improved PFS (HR = 0.77, 95% CI 0.68–0.88, P < 0.001) but not OS (HR = 0.98, 95% CI 0.78–1.24, P = 0.87). Bortezomib-based consolidation/maintenance therapy led to a trend toward increased risk of grade ≥ 3 neurologic symptoms, gastrointestinal symptoms, and fatigue. More research is warranted to further assess the role of bortezomib-based consolidation and maintenance therapy for multiple myeloma.